Whole genome analysis of Bacillus velezensis YNK-FB0059 and its multifunctional plant growth-promoting and biocontrol potential - Liu, Ende; Chen, Yan; Yao, Yuchun; Pei, Weihua; Pu, Te; Shi, Zhufeng; Cao, Yanru; Yang, Peiwen (Frontiers in Microbiology, 2026)
IntroductionThis study conducted a systematic investigation of Bacillus velezensis YNK-FB0059 from genome to phenotype, aiming to comprehensively elucidate its genetic basis and functional traits through whole-genome sequencing and multi-dimensional in vitro validation experiments, thereby revealing its great potential as a multifunctional agricultural microorganism.MethodsWhole-genome sequencing combined with multi-platform bioinformatics analysis was employed to systematically mine secondary metabolite biosynthesis gene clusters, plant growth-promoting genes, and environmental adaptability genes of YNK-FB0059. The complete genome sequence of B. velezensis YNK-FB0059 has been deposited in the GenBank database under the accession number CP140613.1. Targeted experiments were designed and conducted, including plate confrontation assays against pathogenic microorganisms, spore germination and mycelial growth inhibition tests, assessments of phosphorus and potassium solubilization and nitrogen fixation capabilities, detection of siderophore and IAA secretion, biofilm formation analysis, and seed germination and pot-based growth promotion experiments.ResultsGenomic analysis revealed that YNK-FB0059 has a chromosome size of 4.02 Mb, containing 14 secondary metabolite biosynthesis gene clusters encoding various antimicrobial substances such as surfactin, fengycin, bacilysin, and macrolactin H. Complete plant immunity activation gene systems (e.g., flagellin, chemotaxis proteins) and multiple growth-promoting pathways (e.g., nitrogen and sulfur metabolism, tryptophan synthesis) were also identified. In vitro experiments demonstrated that YNK-FB0059 exhibited broad-spectrum antifungal activity against eight important plant pathogenic fungi (inhibition rate: 77.8–88.6%). Its fermentation broth significantly inhibited pathogen spore germination, with a 24-h inhibition rate of 68.35%, and caused mycelial deformation and breakage. Additionally, YNK-FB0059 showed efficient phosphorus and potassium solubilization, nitrogen fixation, siderophore production, and IAA secretion (42.55 μg·mL−1 after 48 h). Biofilm formation reached 148 mg, and it significantly promoted seed germination and seedling growth in crops such as tomato and rapeseed.DiscussionPhylogenetic analysis combined with ANI/dDDH values confirmed its identity as B. velezensis. B. velezensis YNK-FB0059 exhibits excellent integrated traits of biocontrol, growth promotion, and rhizosphere colonization. Its rich secondary metabolite blueprint and complete genetic foundation for plant interaction make it an ideal candidate for developing efficient biopesticides and biofertilizers, holding significant application value in sustainable agricultural development.